A Market Basket Folklore Survey of Ethnobotanical Usage of Plants for Treatment of Mumps in North India - Gunpreet Kaur; Parveen Bansal; Ravinder Sharma; Amar Nath; Vikas Gupta (Mary Ann Liebert, 2022)
Background: Folklore surveys had been a source of development of potential new drugs all over the world. Mumps is a keen extensive disease caused by virus with well-recognized symptoms and complications. In India, a number of herbal drugs have been used as home remedies to cure mumps. This study aimed to create an inventory of the folklore use of medicinal plants in the treatment of mumps in selected states in north India. Methods: A survey was carried out by using a questionnaire on 98 subjects involved in traditional medication in Uttar Pradesh, Himachal Pradesh, Punjab, Uttrakhand, and Union Territories of Chandigarh. Botanical information regarding recognized plants was collected properly and data were further analyzed by using the relative frequency of citation (RFC). Results: As per survey, 23 plant species from 16 families were identified, and the most commonly used plant for treatment of mumps was found to be Glycyrrhiza glabra with RFC value 0.877 followed by Curcuma longa (0.867). It is pertinent to mention that only one clinical study has been done on Mimosa pudica plant with RFC value 0.622 by scientists to support its use in treatment of mumps out of 23 plants reported by traditional healers. Conclusion: This survey expresses the knowledge about medicinal plants used in the treatment of mumps in north India, and it serves as a template for researchers to conduct future research on these plants for mumps treatment.